No evidence for tephra in Greenland from the historic eruption of Vesuvius in 79?CE: implications for geochronology and paleoclimatology - Tomlinson, Emma (My University, 2022)
Volcanic fallout in polar ice sheets provides important opportunities to date and correlate ice-core records as well as to investigate the environmental impacts of eruptions. Only the geochemical characterization of volcanic ash (tephra) embedded in the ice strata can confirm the source of the eruption, however, and is a requisite if historical eruption ages are to be used as valid chronological checks on annual ice layer counting. Here we report the investigation of ash particles in a Greenland ice core that are associated with a volcanic sulfuric acid layer previously attributed to the 79 CE eruption of Vesuvius. Major and trace element composition of the particles indicates that the tephra does not derive from Vesuvius but most likely originates from an unidentified eruption in the Aleutian arc. Using ash dispersal modeling, we find that only an eruption large enough to include stratospheric injection is likely to account for the sizable (24–85 µm) ash particles observed in the Greenland ice at this time. Despite its likely explosivity, this event does not appear to have triggered significant climate perturbations, unlike some other large extratropical eruptions. In light of a recent re-evaluation of the Greenland ice-core chronologies, our findings further challenge the previous assignation of this volcanic event to 79 CE. We highlight the need for the revised Common Era ice-core chronology to be formally accepted by the wider ice-core and climate modeling communities in order to ensure robust age linkages to precisely dated historical and paleoclimate proxy records.
PUBLISHED
Keywords: Volcanic eruption; Greenland ice core; Vesuvius